ANALISIS KETERAMPILAN BERPIKIR KRITIS SISWA MELALUI MODEL PROBLEM-BASED LEARNING (PBL) PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM DI SMA: STUDI LITERATUR - Raudah Azzahra; Patricia Anya Devista; Aryo Dwi Nugroho; Ahyatul Ihsan; M. Nur Ikhsan; Mukhtar Latif (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Critical thinking skills are one of the essential competencies that students must possess in the 21st century, including in Islamic Religious Education (PAI) instruction. However, the PAI learning process in schools is still often dominated by conventional methods that do little to encourage students to analyze, evaluate, and solve problems critically. One learning model considered capable of developing these skills is Problem-Based Learning (PBL). This study aims to analyze the application of the Problem-Based Learning (PBL) model in enhancing students’ critical thinking skills in Islamic Religious Education classes at high school based on various previous research findings. The study employed a qualitative approach using the library research method. Data were obtained by searching for and reviewing various scholarly sources, including journal articles, books, conference proceedings, and academic documents relevant to the research topic. Data analysis was conducted using content analysis techniques through the stages of data reduction, data presentation, interpretation, and drawing conclusions. The results of the study indicate that the implementation of the PBL model contributes positively to the improvement of students’ critical thinking skills, as evidenced by enhanced abilities to analyze problems, present arguments, evaluate information, make decisions, and solve problems systematically. Furthermore, PBL fosters more active, collaborative, and contextual learning, thereby supporting the achievement of Islamic Religious Education learning objectives. The success of PBL implementation is influenced by teacher competence, student readiness, and adequate support from the learning environment